Why the Readiness Potential Does Not Disprove Free Will - Totland, Even (Stance: an international undergraduate philosophy journal, 2021)
Neuroscientist Benjamin Libet has conducted a series of experiments that reveal the existence of certain neural processes in the brain of human subjects, initiating an action prior to the human subject’s intention to act, thus seemingly threatening our idea of free will. The purpose of this paper is to show how these processes do not disprove any idea of free will one might have as one would, if accepting such a thesis, be committing two distinct mereological fallacies and ultimately, would treat the human subject as inhabiting some of its parts as opposed to being the sum of its parts.